Reverse detection for spectral width improvements in spatially encoded dimensions of ultrafast two‐dimensional NMR spectra. (7th August 2014) - Wei, Zhiliang; Yang, Jian; Lin, Liangjie; Liu, Guangcao; Lin, Yanqin; Chen, Zhong
<x xml:space="preserve">Abstract</x> Recently, the spatially encoded technique has been broadly used in the fast analyses of chemical systems and real‐time detections of chemical reactions. In spatially encoded ultrafast 2D spectra, spectral widths and resolution in spatially encoded dimensions are contradictive, leading to the risk of insufficient spectral widths when providing satisfactory resolution values for all resonances. Here, a method named as reverse detection is proposed to improve the spectral width in the spatially encoded dimension. Experimental results show that spectral width improvements are at least twofold with reverse detection solely, and more improvements can be expected along with the gradient‐controlled folding method. The proposed method can be applied to almost any spatially encoded scheme with echo planar spectroscopic imaging—like detection module and may promote wide applications of ultrafast 2D spectroscopy techniques in chemical analyses. Copyright © 2014 John Wiley & Sons, Ltd.